Integrated perspectives on the use of bacterial endophytes in horizontal flow constructed wetlands for the treatment of liquid textile effluent: Phytoremediation advances in the field. (15th October 2018) - Hussain, Zahid; Arslan, Muhammad; Malik, Mumtaz Hasan; Mohsin, Muhammad; Iqbal, Samina; Afzal, Muhammad
Abstract: Constructed wetlands (CWs) have emerged as cost-effective and sustainable treatment systems for the remediation of industrial wastewaters; nevertheless, their potential has mostly been evaluated in laboratory-scale studies. Likewise, endophytic bacteria can enhance plant growth and reduce phytotoxicity under polluted conditions, but their application with pilot-scale CWs has rarely been evaluated. The present study aims to evaluate on-site performance of endophyte-assisted pilot-scale horizontal flow constructed wetlands (HFCWs) for the remediation of effluent from a textile industry. The HFCWs were established by planting Leptochloa fusca in the presence of three endophytic bacterial strains with dye degrading, and plant growth promoting capabilities. We found that the system was able to remove a significant proportion of both organic and inorganic pollutants. Maximum reduction of pollutants was observed in endophyte-augmented HFCWs, where the COD and BOD reduced from 493 to 70 mg l −1 and 190 to 42 mg l −1, respectively, within 48 h. Additionally, survival of endophytic bacteria in different components of the HFCWs was also recorded. Treated wastewater was found to be non-toxic and the inoculated bacteria showed persistence in the wastewater as well as rhizo- and endosphere of L. fusca . Accordingly, a positive impact on plant growth was observed in the presence of bacterial augmentation. The system performance was comparable to the vertical flow constructed wetlands (VFCWs) as high nutrients reduction was seen in the presence of this partnership. This pilot-scale study is a step forward toward the field-scale application of phytoremediation coupled with bacterial endophytes as a cost-effective means of on-site wastewater remediation. To the best of our knowledge, this is among the first pilot-scale studies on use of HFCWs for improvement in quality of textile industry effluent as most previous studies are limited either in the context of engineering or lack effective interplay of plant and bacteria. Graphical abstract: Image 1 Highlights: Pilot-scale endophyte-assisted HFCWs was used to treat textile industry wastewater. Endophytes augmentation in CW enhanced its pollutants removal efficacy. Endophytes assisted HFCWs can attain high nutrients reduction comparable to the VFCWs. The present study is a step forward toward the field-scale application of phytoremediation.